Subspecies and Distribution. L. l. lynx Linnaeus, 1758 — N and W Europe E to the Yenisei River in Russia. L. l. carpathicus Kratochvil & Stollman, 1963 — Carpathian Mts S to Bulgaria and Greece. L. l. dinniki Satunin, 1915 — Caucasus Mts S to Turkey and N Iran. L. l. isabellinus Blyth, 1847 — Pamir and Kunlun Mts, Kashmir, C & W China. L. l. kozlovi Fetisov, 1950 — C Siberia, from the R Yenisei to Lake Baikal. L. l. neglectus Stroganov, 1962 — Russian Far East, Korea, and NE China (Manchuria). L. l. wrangeli Ognev, 1928 — E Siberia, S to the Stanovoy Mts. in Felidae - Wilson, Don E.; Mittermeier, Russell A. (Zenodo, 2009)
Subspecies and Distribution. L. l. lynx Linnaeus, 1758 — N and W Europe E to the Yenisei River in Russia. L. l. carpathicus Kratochvil & Stollman, 1963 — Carpathian Mts S to Bulgaria and Greece. L. l. dinniki Satunin, 1915 — Caucasus Mts S to Turkey and N Iran. L. l. isabellinus Blyth, 1847 — Pamir and Kunlun Mts, Kashmir, C & W China. L. l. kozlovi Fetisov, 1950 — C Siberia, from the R Yenisei to Lake Baikal. L. l. neglectus Stroganov, 1962 — Russian Far East, Korea, and NE China (Manchuria). L. l. wrangeli Ognev, 1928 — E Siberia, S to the Stanovoy Mts. : Published as part of Don E. Wilson & Russell A. Mittermeier, 2009, Felidae, pp. 54-168 in Handbook of the Mammals of the World – Volume 1 Carnivores, Barcelona :Lynx Edicions on page 151, DOI: 10.5281/zenodo.6376899